1995
DOI: 10.1042/bj3050439
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and heterologous expression of a cDNA encoding pigeon liver carnitine acetyltransferase

Abstract: Two overlapping cDNA clones encoding pigeon liver carnitine acetyltransferase (EC 2.3.1.7) (CAT) were isolated from a pigeon liver lambda gt11 cDNA library by gene amplification using oligonucleotide primers based on the N-terminal amino acid sequence of the enzyme. The two clones, which represent the 5' and 3' ends of the gene, were spliced together to form a single cDNA construct containing the entire coding sequence for CAT, with an in-frame TGA stop codon 42 bases before the first ATG start site and a 3'-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…If no other processing occurred, molecular sizes of 68191 Da for the peroxisomal enzyme and 66446Da for the mitochondrial enzyme would be expected from the deduced amino acid sequences. The apparent molecular masses measured by SDS/PAGE (64 kDa) were smaller than those predicted from the sequences, a tendency which was also demonstrated for the pigeon liver enzyme [31]. These results revealed that initiation of translation for peroxisomal carnitine acetyltransferase was at the second Met residue (Metl9) (Fig.…”
Section: Peroxisomal and Mitochondrial Carnitine Acetyltransferasesmentioning
confidence: 63%
“…If no other processing occurred, molecular sizes of 68191 Da for the peroxisomal enzyme and 66446Da for the mitochondrial enzyme would be expected from the deduced amino acid sequences. The apparent molecular masses measured by SDS/PAGE (64 kDa) were smaller than those predicted from the sequences, a tendency which was also demonstrated for the pigeon liver enzyme [31]. These results revealed that initiation of translation for peroxisomal carnitine acetyltransferase was at the second Met residue (Metl9) (Fig.…”
Section: Peroxisomal and Mitochondrial Carnitine Acetyltransferasesmentioning
confidence: 63%
“…(Esser et al, 1993;L07736), rat CPT-I-like (Yamazaki et a]., 1995; D43623), human CPT-I1 (Finocchiaro et al, 1991;M58581), rat CPT-I1 (Woeltje et al, 1990;J05470), mouse CPT-I1 (Gelb, 1993;U01163), rat COT (Choi et al, 1995;U26033), bovine COT (this study), mouse CAT (Brunner et a]., 1997; X85983), pigeon CAT (Johnson et al, 1995;U08229), yeast CAT (Kispal G., Tomcsanyi, T., Sumegi, B., Bock, I., Gajdos, G., Dietmayer, K. and Sandor, A., 1992;214021), human ChAT (Oda et al, 1992;S56138), rat ChAT (Ishii et al, 1990;P32738), pig ChAT (Berrard et a]., 1989; M27736), C. elegans ChAT (Alfonso et al, 1994;L08969) and D. melanogaster ChAT (Sugihara et a]., 1990; M63724) were aligned using Clustal V (Higgins et a]., 1992) (all accession numbers are GenBank entries with the exception of rat ChAT, which is a SwissProt database entry).…”
Section: Ss'mentioning
confidence: 99%
“…1) showed ∼ 53% nucleotide sequence identity to carnitine acetyltransferase genes from human (Corti et al 1994) and pigeon (Johnson et al 1995). Similar levels of identity were found across about two thirds of the sequence to choline acetyltransferase genes from pig (Berrard et al 1987(Berrard et al , 1989 and human (Lorenzi et al 1992).…”
mentioning
confidence: 49%